Analisis Hukuman Matilda Dalam Novel Roald Dahl Dari Perspektif Psikologis - Suwastini, Ni Komang Arie; Mahendrayani, Kadek Leny; Utami, Ida Ayu Made Istri; Myartawan, Putu Ngurah Wage; Asril, Nice Maylani (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2023)
Roald Dahl's novel Matilda features a child with a strong penchant for punishing adults. Using Erikson’s concept of children’s development, the present study aimed to explain why Matilda was described as a five-year-old girl to perform those punishments. Through textual analysis, the present study revealed that Matilda developed as a girl who administered punishments to adults around her as part of her development at the play age. At this age, a child learns to set specific goals and plan to achieve them. In the novel, this development is reflected in Matilda Wormwood’s goal to punish her father as described in chapters “The Hat and the Superglue,” “The Ghost,” and “The Platinum-Blonde Man.” Matilda’s punishments in this novel send a strong message to readers that parents should provide good examples and sufficient attention to their children when they start learning to set goals, especially when they are very intelligent and have strong potential like Matilda.